In vivo methods for acute modulation of gene expression in the central nervous system. (September 2018) - Cwetsch, Andrzej W.; Pinto, Bruno; Savardi, Annalisa; Cancedda, Laura
Highlights: An overview of chemical methods for in vivo transfection, having high-packaging capacity, low immunogenicity and toxicity. An overview of physical methods for in vivo transfection, having low cost and toxicity. An overview of virus types for in vivo transduction, having high efficiency and specificity for specific cellular types. A discussion on the potentials of combining methods for in vivo transfection with emerging molecular biology techniques. A discussion on the ongoing and potential applications of in vivo transfection in gene therapy. Abstract: Accurate and timely expression of specific genes guarantees the healthy development and function of the brain. Indeed, variations in the correct amount or timing of gene expression lead to improper development and/or pathological conditions. Almost forty years after the first successful gene transfection in in vitro cell cultures, it is currently possible to regulate gene expression in an area-specific manner at any step of central nervous system development and in adulthood in experimental animals in vivo, even overcoming the very poor accessibility of the brain. Here, we will review the diverse approaches for acute gene transfer in vivo, highlighting their advantages and disadvantages with respect to the efficiency and specificity of transfection as well as to brain accessibility. In particular, we will present well-established chemical, physical and virus-based approaches suitable for different animal models, pointing out their current and future possible applications in basic and translational research as well as in gene therapy.